Analisis Perubahan Tutupan Lahan Menggunakan Citra Satelit Landsat di Kawasan Hutan Dengan Tujuan Khusus Sisimeni Sanam Tahun 2021 - Dimas Christyan Pratama Arka; Maria M. E. Purnama; Fadlan Pramatana (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2024)
Sisimeni Sanam has several problems, such as slashing, burning, and land clearing from local community. In addition, forest and land fires also occurred in Sisimeni Sanam area. This research was conducted to monitor the changes of land cover in the Sisimeni Sanam, East Nusa Tenggara Province from March to April 2022 All the data from this study was analyzed with quantitative analysis that utilizes remote sensing data so that can be interpreted satellite imagery. The method used in this research is OBIS (Object Based Image Segmentation) in order to determine the area of land cover 2021 in the Sisimeni Sanam. In 2021, the value of land cover in the Sisimeni Sanam Special Purpose Forest Area has land cover in the dense forest class of 241.03 Ha (8%), medium forest of 991.04 Ha (33%), shrubs of 1453.31 Ha (49%), and open land pad of 287.82 Ha (10%).